What Is The Benefit Of Tourism Branding? Analysis of Digital Marketing Tourism Branding Based in Fatumnasi Village, Indonesia - Lenny Sofia Bire Manoe; Chris Oiladang; Imanta I. Perangin Angin; Hildigardis M.I Nahak (Journal of Tourism and Economic, 2025)
This study explores the benefits of tourism branding through the lens of digital marketing in Fatumnasi Village, located in the south east timor district, East Nusa Tenggara. This will influence the spread of information about tourist destinations in Fatumnasi Village, boost tourist visits, raise public awareness about the use of information technology (Instagram social media platform), and identify suitable solutions for the sociological analysis of rural tourism development. The qualitative method employs a case study as its research method. Data collected through in-depth interviews, focus group discussions, literature review and analyzed using triangulation method. The results indicated a lack of digital marketing-based tourism branding, which could be attributed to the management of the Mutis Timau nature reserve tourist attraction and the low participation of the village community in implementing the agro tourism. Furthermore, the village government and community of Fatumnasi Village have limited knowledge about digital marketing-based village tourism branding, which hinders their participation in the development of tourism villages. The challenges in tourism branding include limited infrastructure, road access, tourist support facilities, and a lack of tourism training and education for the local community. The community's active involvement and the appropriate strategy are crucial in maximizing this positive impact.